Optimization Model for the Russian Electric Power Generation Structure to Reduce Energy Intensity of the Economy - Semin, Alexander N.; Ponkratov, Vadim V.; Levchenko, Kirill G.; Pozdnyaev, Andrey S.; Kuznetsov, Nikolay V.; Lenkova, Olga V. (International Journal of Energy Economics and Policy, 2019)
In the context of high energy intensity of the country's economy, contributing to a decrease in the industry competitiveness of the Russian Federation, it is relevant to develop scientific approaches to energy efficiency provision. The article is aimed at stimulating the optimal structure of electric power generation in Russia, promoting energy conservation and lowering energy intensity of the economy. The Cobb-Douglas production function was used to determine the dependence of the gross electric output on such production factors as labor costs and capital. Based on the expert evaluation method, the sources of electricity generation were differentiated according to the level of labor intensity. An optimization model has been developed for electric power generation structure in Russia in the context of actual energy generation sources: nuclear power plants; natural gas fired thermal power plants , coal and fuel oil fired power plants; hydropower plants; solar power plants; wind power plants; tidal power plants; and biofuel power plants. The percentage changes in the consumption of energy resources and power generation, ensuring a decrease in the energy intensity of the Russian Gross Domestic Product by 19.1%, are argued. The system of optimization measures has been substantiated; their practical implementation will contribute to the steady decline in energy intensity of the Russian economy, effective energy consumption and the growth of the country's energy potential, with regard to ensuring structural changes in the energy sector. Keywords: Energy Intensity of the Russian Economy, Energy Resources, Optimization Model for Electric Power Generation Structure, Power Industry, Economic Energy Efficiency JEL Classifications: Q4; L16; L52 DOI: https://doi.org/10.32479/ijeep.7552